The genom of enteroviruses in the blood serum of patients with acute stroke. - N. G. Andryushkova; N. S. Turchin; L. V. Dolinchuk; V. A. Ponyatovskyy; V. V. Melnik; V. P. Shyrobokov; L. N. Trepet (Medičnì Perspektivi, 2016)
Objective of the study was determination of enterovirus genom presence in the blood serum of patients with acute stroke by polymerase chain reaction (PCR). The blood serum of 72 patients with acute stroke and control group of 30 patients with another vascular disease was studied to reveal genom of enteroviruses. Detection of enterovirus RNA was performed by PCR using the reverse transcription. Viruses were isolated on HeLa and HEp-2 cell lines. The enterovirus genom detected by PCR was in 17 of 72 samples of the tested serum in the research group (23,6±5,0%). In the control group only one serum was PCR-positive for enteroviruses (3,3±3,2%). Cytopathogenic agents were isolated in HEp-2 and HeLa cell lines from 11 PCR-positive samples of blood serum from the experimental group of patients. No viruses were isolated from the remaining PCR-positive and PCR-negative sera. The presence of enteroviruses in the blood of patients with acute stroke suggests etiopathogenetical link between them. The introduction of PCR to detect enteroviral agents in patients with acute stroke can complement existing methods of diagnosis.